Dosimetric comparison of complete block in ovarian protection between helical tomotherapy and volumetric-modulated arc therapy for cervical cancer. Issue 1 (March 2022) - Liu, Xianfeng; Wu, Furong; Jin, Fu; Sun, Fu; Li, Qicheng; Guo, Mingfang; Zhao, Xiujuan; Guo, Qishuai
Abstract: This study is aimed at comparing the dosimetric differences of restricting beamlets passing in protecting ovaries between helical tomotherapy (HT) and volumetric-modulated arc therapy (VMAT) for patients with cervical cancer, and particularly comparing the γ passing rates of ovaries between the two techniques by independent dose calculations. 15 patients with cervical cancer who had undergone ovarian transposition were randomly enrolled. The HT and VMAT plans were created for each involved patient. Target quality, organs at risk (OARs) sparing, and γ passing rates of ovaries were compared between HT and VMAT. HT achieved better than VMAT in D98%, D2%, Dmean, conformal index and homogeneity index (P < 0.05). Almost all OARs in HT had lower radiation dose than those in VMAT (P < 0.05). All the γ passing rates of the ovaries were 100% for the 15 patients both in HT and VMAT. The results suggests that HT outperforms VMAT in terms of target coverage and OARs sparing. Although the calculated dose to the ovaries was accurate both in HT and VMAT, HT showed further advantages for cervical cancer patients with ovarian protection requirements.